MATHEMATICAL AND COMPUTER-BASED SIMULATION OF INDUSTRIAL ENVIRONMENT GENERATION FOR THE PURPOSES OF PLANNING AND OPTIMIZATION OF AREA VENTILATION SYSTEMS - Besarion Chokhoyevich Meskhi; Yury Igorevich Bulygin; Alexander Nikolayevich Legkonogikh; Anatoly Leonidovich Gaydenko (Advanced Engineering Research, 2014)
The dominant occupational hazards at the welding sites are identified. They are elevated air pollution and dustiness. Depending on the welding forms, the concentrations of harmful substances (carbon oxide, iron and magnesium oxides) exceed the sanitary-hygienic standards by 7‒10 times. The heat and mass transfer of harmful substances and heat in the industrial environment with dynamic ventilation and pollutant sources is considered. Its nonstationary 3D mathematical model is presented. The model permits the turbulence of air flows which differs it from the existing models of the occupational hazard spread. The developed software enables to solve various tasks of the ventilation system installation and operation. Specifically, it is referred to the rational distribution of various engineering devices of the given system, its control issues, and of the optimal worksite location. To ensure safe working conditions for the welding operators, the recommendations on the rational organization of the local ventilation system operation are developed. The corresponding constructive solutions are proposed.